Simultaneous measurement of space-dependent refractive index and absorption coefficient based on a laser irradiation technique. (6th September 2018) - Wei, Lin-Yang; Qi, Hong; Sadaf, Arafat Islam; Wen, Shuang; Ruan, Li-Ming
Abstract: An investigation of simultaneous measurement of the space-dependent refractive index and absorption coefficient in semitransparent materials is carried out in this work. The transient coupled radiation–conduction problem in absorbing, emitting semitransparent media exposed to laser irradiation as the direct model is solved by the finite volume method. A hybrid stochastic particle swarm optimization and differential evolution (SPSO-DE) algorithm is proposed to improve the search ability and computation efficiency of the inverse technique, in which the DE algorithm is employed to improve the individual best position in the SPSO search procedure. As the radiative response at the boundary is highly sensitive to the refractive index but only slightly sensitive to the absorption coefficient, the space-dependent refractive index and absorption coefficient are difficult to estimate simultaneously. A two-step inverse model with different laser irradiation is proposed to overcome this difficulty. All the estimated results show that the proposed two-step inverse model performs accurately and effectively.